If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + -14 = 40 Reorder the terms: -14 + 3u = 40 Solving -14 + 3u = 40 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 3u = 40 + 14 Combine like terms: -14 + 14 = 0 0 + 3u = 40 + 14 3u = 40 + 14 Combine like terms: 40 + 14 = 54 3u = 54 Divide each side by '3'. u = 18 Simplifying u = 18
| -32=-35-5n^2 | | 6=2v-16 | | 5x-2=7(2x-8) | | 2y-15=19 | | 7n^2-11n=-4 | | 9+16-9(1)2= | | r^2-4r-15=-3 | | x/9=1/6 | | 3lnx-lny=0 | | (Y-18)/6=0.7 | | -3(-5-b)=.33(b+13) | | (Y-18)/6 | | 12+8k=84 | | Y-18/6 | | 0.6(t+36)=-3(4-t) | | 19x+(-9)=-29+14x | | 12b+12b=3 | | 5/8x40 | | 9-w=215 | | 1/3.(180-×) | | 3y-15=33 | | (7-7x^2)/7 | | 12x+42=10x+50 | | 17x-1=135 | | X^2-20-3x-20=0 | | 12x-6+6=36 | | 1/-76=1/x | | -2x+8=4(x+8) | | 7=(-3)+x | | 12x+42=10x+56 | | 0.4+8=12 | | -9=2(w+3)-5w |